Chemical composition of flesh of diploid and triploid population of tench (Tinca tinca, Linnaeus 1758) - H. Buchtová; L. Vorlová; Z. Svobodová; M. Flajšhans (Czech Journal of Animal Science, 2005)
The objective of this study was to determine differences in relevant parameters of the basic chemical composition of flesh (descriptors: dry matter - DM, crude proteins - CP, net proteins - NP and net muscle proteins - NMP, fat - F, ash - A) of communal stock of diploid (2n) and triploid (3n) tench (Tinca tinca L.) of the same origin, in relation to sex (F: female vs. M: male) and age (T3: 36 months, after overwintering vs. T3+: 42 months, after one summer in the pond). Altogether 137 siblings of tench were studied. The basic chemical composition of flesh of 2n and 3n tench of T3 age was found to be nearly the same. The only significant difference (P < 0.05) was found in DM content in diploids (5.7% higher DM content in females). Marked changes in the basic chemical composition were related to the increasing age of tench: after one summer in the pond (from T3 to T3+) the DM content increased significantly in all groups of tench (by 5.4% in 2n females, P < 0.05; by 6.5% in 2n males, 9.9% in 3n females and by 7.4% in 3n males, all at P < 0.01). The content of nitrogenous substances was found to increase significantly (P < 0.01) in flesh of 2n males: CP by 3.2%, NP by 4.2% and NMP by 3.3% and in flesh of 3n males: CP by 7.0%, NP by 6.6% and NMP by 7.3%. Muscles of 3n females contained 107.3% higher fat content (P < 0.05). The proportion of ash decreased in 2n and 3n by 2.5% and 1.7%, respectively (P < 0.05). The flesh quality of T3+ tench after one summer in the pond was higher if compared with that of T3 tench after overwintering. Related to the ploidy level, more favourable chemical composition of flesh and more favourable flesh quality were found for triploids of T3+ age.